Perceived faculty development needs and motivations of Chinese general practice trainers: a narrative review of the literature - Timothy Noel Stephens; Susan Somerville (BMC Medical Education)
Abstract Background Like other countries developing standardized general practice training, China faces the challenge of training vast numbers of new general practice faculty. However, little is known about these clinician-teachers’ motivations and perceived needs for faculty development. This review intended to explore available published data on Chinese general practice faculty development needs and motivation for ongoing professional development. Methods A systematic search was conducted using combinations of keyword and MeSH term searches in English in PubMed and in Chinese language CNKI and WanFang databases, followed by a qualitative narrative synthesis of relevant articles identified. Inclusion criteria: English or Chinese publications between 1990 and 2021; qualitative or quantitative research, systematic reviews, literature reviews, review or opinion articles pertaining to faculty development or professional development needs or motivations of general practice or family medicine teachers. Articles pertaining to fields outside of medicine, those with a heavy subspecialty focus or not relevant to primary care were excluded. Results A total of 88 full text articles were included in this review. Available data on Chinese general practice faculty development needs placed emphasis on fundamental general practice knowledge, principles, and clinical training needs more than teaching and assessment skills. Learning through teaching and a sense of responsibility were potential sources of intrinsic motivation for pursuing faculty development. Potential barriers to participation included busy workloads, inadequate organizational support, and limited finances. Mandatory participation, irrelevant content, lack of teaching experience, lack of motivation to teach, and overall job dissatisfaction appeared to negatively influence motivation to pursue faculty development. Conclusions Further research should explore the broader continuous professional development needs of this large population of general practice teachers. Qualitative studies are needed to clarify how individual, organizational, and contextual factors influence teachers’ motivation to pursue faculty development.